One pot and single step hydrolytic process for the conversion of lignocellulose into value added chemicals - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (WO2011092711 A1, 2011)
The present invention provides a single step hydrolytic process for the conversion of lignocellulose, into value added chemicals wherein said process is catalyzed by at least one heterogeneous solid acid catalyst selected from a group comprising of zeolites, zeolites with Si/metal, mesoporous silica, oxides and phosphates, clays, ion-exchange resins, heteropolyacids, various sulfates, phosphates, selenates, crystalline materials and amorphous materials.